2004
DOI: 10.1111/j.1540-627x.2004.00099.x
|View full text |Cite
|
Sign up to set email alerts
|

Sources of Bioentrepreneurship: The Cases of Germany and Japan

Abstract: The application fields of biotechnology are as diverse as healthcare, chemistry, material science, agriculture, and environmental protection. There exist nearly 1,300 biotechnology companies in the United States, providing employment to approximately 150,000 people. Today, most of these biotechnology firms in the United States are still relatively small, with approximately two-thirds employing fewer than 150 people and are located within a cluster of biotechnology companies, for example, in the areas of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 14 publications
2
33
0
1
Order By: Relevance
“…In some smaller sub-sectors, such as biotechnology, spin-offs grow rapidly and dominate the industry. The same goes for other sectors, such as optics, medical technologies and information technologies (Egeln et al 2002;Müller et al 2004).…”
Section: Introductionmentioning
confidence: 92%
“…In some smaller sub-sectors, such as biotechnology, spin-offs grow rapidly and dominate the industry. The same goes for other sectors, such as optics, medical technologies and information technologies (Egeln et al 2002;Müller et al 2004).…”
Section: Introductionmentioning
confidence: 92%
“…Moreover, these few firms belong mostly to established industries, such as machinery, wholesale and retail, and less to new business or technology sectors (Nakagawa, 1999). New sectors are, if at all, founded by affiliated keiretsu-firms (enterprise groups), as Müller et al (2004) found for the biotechnology industry. The OECD (2006: 10), therefore, recommended that the 'focus [of] support for R&D [should be] on new start-ups rather than on existing companies as it is now the case'.…”
Section: Context: the Nature Of Japan's Competitivenessmentioning
confidence: 98%
“…Parent company outposts will be run as appendages of the multinational, reflecting the subsidiary's role in accessing a host‐country subsidy (Wilson, ), testing facilities, less restrictive health or environmental regulations (Müller, Fujiwara and Herstatt, ; Witt and Lewin, ) or lower‐cost talent (Manning, Sydow and Windeler, ). Because parent company outposts take advantage of an aspect of a host‐country's innovation system that does not require the subsidiary to be strongly embedded locally, any local personnel are unlikely to have much authority and will probably not have organizational careers or stock options.…”
Section: Internal and External Embeddedness And The Development Of Kmentioning
confidence: 99%